History and Cultural Memory in Neo-Victorian Fiction - Mitchell, Kate (Springer Nature, 2010)
History and Cultural Memory in Neo-Victorian Fiction combines innovative literary and historiographical analysis to investigate the way neo-Victorian novels conceptualise our relationship to the Victorian past, and to analyse their role in the production and communication of historical knowledge. Positioning neo-Victorian novels as dynamic participants in the contemporary historical imaginary, it explores their use of the Victorians' own vocabularies of history, memory and loss to re-member the nineteenth century today. While her focus is neo-Victorian fiction, Mitchell positions these novels in relation to debates about historical fiction's contribution to historical knowledge since the eighteenth century. Her use of memory discourse as a framework for understanding the ways in which they do lay claim to historical recollection, one which opens up a range of questions beyond historical fidelity on the one hand, and the problematics of representation on the other, suggests new ways of thinking about contemporary historical fiction and its prevalence, popular appeal, and nmnenonic function today.